The identification, purification and characterization of the fetal rat liver glutathione S-transferase isoenzyme YcYfetus - Scott, Trevor Robert (UCT/MRC Liver Research Centre, 2018)
This study has examined the expression of the glutathione S-transferases (GSH S-T) in fetal rat livers in order to provide more information about the role played by this important group of enzymes in the fetus. The study commenced with an examination of the subunit composition of adult and fetal rat liver GSH S-T using affinity chromatography followed by polyacrylamide gel electrophoresis in sodium dodecyl sulphate. Adult livers contained four major GSH S-T subunits. An additional and previously unidentified subunit was detected in fetal livers. This subunit, which differed from that found in rat placenta, had a Mᵣ of approximately 25 500. Densitometric measurements suggest that the newly detected subunit accounts for as much as 26% of the GSH S-T in fetal livers. The novel fetal isoenzyme comprising this subunit was purified using a combination of affinity chromatography, carboxymethyl-cellulose column chromatography and chromatofocusing. The six major basic rat liver GSH S-T were purified for reference and comparative purposes. The fetal isoenzyme is composed of two non-identical subunits, namely, subunit Yc (Mᵣ 28 000) and the fetal subunit referred to as 'Yfetus'· The enzyme which I have termed GSH S-transferase Yc Y fetus has an isoelectric point of approximately 8.65 and has GSH S-T activity towards a number of substrates. Significantly, the fetal isoenzyme has one of the highest glutathione peroxidase activities yet described for the purified rat liver GSH S-T towards the model substrate, cumene hydroperoxide. Kinetic studies reveal that the fetal isoenzyme has a catalytic efficiency for the peroxide substrate which is four fold higher than that of the adult rat liver isoenzyme, GSH S-T YcYc. The in vitro effect of the GSH S-T substrate and teratogen, acrolein, on this fetal isoenzyme was investigated and compared with acrolein's effect on some of the adult rat liver GSH S-T isoenzymes in the standard 1-chloro-2,4-dinitrobenzene assay. Surprisingly, acrolein was identified as a non-competitive inhibitor of the GSH S-T. Exposure to acrolein in various guises could therefore result in inhibition of the fetal isoenzyme and its subsequent failure in inhibiting lipid peroxidation. Inhibitor studies were performed to look at the effect of acrolein, as well as other substrate and non-substrate ligands, on the glutathione peroxidase activity of GSH S-T YcY fetus and YcYc. The glutathione peroxidase activity of the fetal isoenzyme was far less susceptible to acrolein inhibition than the YcYc isoenzyme and the fetal isoenzyme was found to retain significant glutathione peroxidase activity despite saturating concentrations of non-substrate ligand. This study suggests that the fetal isoenzyme serves a specific function in protecting fetuses against the possible teratogenic effects of organic peroxides.